2001
DOI: 10.1021/ac0012647
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Double-Layer Charging of Phenothiazine Functionalized Monolayer-Protected Clusters

Abstract: Monolayer-protected Au clusters (MPCs) have been prepared with mixed monolayers of alkanethiolates and alkanethiolates terminally omega-functionalized with phenothiazine. The mixed monolayer MPCs can contain as many as 10 phenothiazines/MPC; these electron donors are electroactive in rapid, successive one-electron reactions. Surface adsorption of the functionalized MPCs is evident in cyclic voltammetry. Double-potential-step chronocoulometry with incremented potential steps was applied to unfunctionalized hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…Additional papers describe "fluorescent" nanoparticles that are, in fact, polymer nanoparticles that contain organic fluorescent dyes (63). Fundamental electrochemical studies of monolayer-protected gold nanoparticles are in the analytical literature, and there are reports of visible photoluminescence from such species (64,65). Colorimetric detection of analytes using analyte-mediated aggregation of gold nanoparticles to produce a red-to-blue color change has been reported (66).…”
Section: Quantum Dots Versus Other Nanoparticlesmentioning
confidence: 99%
“…Additional papers describe "fluorescent" nanoparticles that are, in fact, polymer nanoparticles that contain organic fluorescent dyes (63). Fundamental electrochemical studies of monolayer-protected gold nanoparticles are in the analytical literature, and there are reports of visible photoluminescence from such species (64,65). Colorimetric detection of analytes using analyte-mediated aggregation of gold nanoparticles to produce a red-to-blue color change has been reported (66).…”
Section: Quantum Dots Versus Other Nanoparticlesmentioning
confidence: 99%
“…New phenothiazine derivatives, substituted at position 10 with alkyl chains bearing thioacetate (8)(9)(10) or mercapto (11-13) groups, were obtained starting from phenothiazine 1 (Scheme 1, Table 1) In the first step the starting compound was alkylated to 10-bromoalkyl phenothiazine compounds using dibromoalkanes [Br-(CH 2 ) n+1 -Br; n = 2, 5, 7]. After several experiments carried out to obtain the compound 2 we concluded that the best results are obtained using Cu / K 2 CO 3 in an alkylation procedure adapted from the literature [13].…”
Section: Resultsmentioning
confidence: 99%
“…To a suspension of lithium aluminium hydride (1.34 mmol, 0.05 g) in dry diethyl ether (10 mL) cooled in an ice bath was added dropwise a solution of 3,7-dibromo-10-alkylthioacetate-phenothiazine (8)(9)(10) [0.67 mmol, 0.31 (8), 0.34 (9), 0.36 g (10)] in dry diethyl ether (20 mL). The mixture was stirred for two hours, then sodium hydroxide solution 20% (2 mL) was added and the reaction mixture was stirred for another half an hour then filtered.…”
Section: General Procedures For the Synthesis Of New Compounds 11-13mentioning
confidence: 99%
See 1 more Smart Citation
“…The MPCs are soluble nanoelectrodes that exhibit various unusual electrochemical properties when compared to functionalized planar electrodes. Murray and co-workers have contributed enormously to the understanding of the electrochemistry of ofunctionalized and unfunctionalized alkanethiolate stabilized Au-cluster compounds [52][53][54][55][56][57][58][59]. Functional groups such as anthraquinone (AQ), ferrocene (Fc), phenothiazine, arenes, esters, acids, alcohols and dithiols of different chain lengths have been incorporated into alkanethiolate modified Au-clusters using the place exchange method [52].…”
Section: Monolayer-protected Nanoclustersmentioning
confidence: 99%